Potassium Fertigation With Deficit Irrigation Improves the Nutritive Quality of Cassava - Wasonga, Daniel O.; Kleemola, Jouko; Alakukku, Laura; Mäkelä, Pirjo S. A. (Frontiers in Sustainable Food Systems, 2020)
Water deficit limits cassava (Manihot esculenta Crantz) productivity in drought-prone areas and alters the nutritive quality of the crop. Potassium (K) may mitigate the effects of water deficit and improve the nutritional content of cassava, which would alleviate malnutrition among the human population in the tropics who depend on cassava as a staple food. Pot experiments were conducted under controlled glasshouse conditions to investigate the influence of deficit irrigation and K fertigation on the nutritive and anti-nutritive quality of biofortified cassava during the early growth phase. Treatments initiated at 30 days after planting were three irrigation doses (30, 60, 100% pot capacity) that were split to five K (0.01, 1, 4, 16, and 32 mM) concentrations. Plants were harvested at 90 days after planting, and the starch, energy, carotenoid, crude protein, fiber, minerals, and cyanide concentration of the leaves and roots were determined. Irrigation and K treatments showed significant (P < 0.05) interactions for starch, carotenoid, energy, and cyanide concentration. An irrigation dose of 30% together with 0.01 mM K resulted in the lowest starch, carotenoid, energy, and fiber content, but highest cyanide concentration, relative to full-irrigated (100%) plants together with 16 mM K. When the K application rate was 16 mM the best nutritional quality was obtained, with the lowest cyanide concentration, regardless of irrigation dose. Moreover, nutritional traits showed strong positive associations, whereas cyanide concentration correlated negatively with all the nutritional traits. Notably, an irrigation dose of 60% together with 16 mM K reduced the nutritional content the least and showed minimal increase in cyanide concentration. The results indicate that K fertigation with adjusted irrigation may improve the dietary quality of young cassava and reduce antinutrients, which could enhance the nutrient bioavailability of cassava grown in drought-prone areas.